Ankylosing Spondylitis Patients Have Impaired Osteoclast Gene Expression in Circulating Osteoclast Precursors - Perpétuo, Inês P.; Caetano-Lopes, Joana; Vieira-Sousa, Elsa; Campanilho-Marques, Raquel; Ponte, Cristina; Khmelinskii, Nikita; Canhão, Helena; Ainola, Mari; Fonseca, João E. (Frontiers in Medicine, 2017)
Introduction: Ankylosing spondylitis (AS) is typically characterized by focal bone overgrowth but also by systemic bone loss. We hypothesize that the increased osteoproliferation found in AS might be partially due to reduced ability of osteoclast precursors (OCPs) to differentiate into osteoclasts (OC). Therefore, our aim was to characterize bone remodeling and pro-osteoclastogenesis inflammatory environment, monocytes phenotype and in vitro osteoclast differentiation in AS patients. Methods: Patients with active AS without any ongoing therapy and age and gender-matched healthy donors were recruited. Receptor activator of nuclear factor-κβ (RANKL) surface expression on circulating leukocytes and frequency and phenotype of monocyte subpopulations were assessed. Quantification of serum levels of bone turnover markers and cytokines, in vitro OC differentiation assay and quantitative reverse transcription real-time PCR for OC specific genes were performed. Results: Pro and anti-inflammatory cytokine serum levels were higher in AS patients than in controls. RANKL neutrophil expression was higher in AS patients when compared to healthy donors, but CD51/CD61 expression was lower in the classical monocyte subpopulation. Concerning osteoclastogenesis, we found no differences in the in vitro osteoclast differentiating potential of these cells when compared to healthy donors. However, we observed low expression of CSF1R, RANK and NFATc1 in AS osteoclast precursors. Conclusions: Despite the high levels of pro-inflammatory cytokines present in AS patients, no differences in the number of OC or resorbed area were found between AS patients and healthy donors. Moreover, we observed that OCPs have low OC specific gene expression. These findings support our hypothesis of an impaired response of OCPs to pro-osteoclastogenic stimuli in vivo in AS patients.